BIMBINGAN TEKNIS BUDIDAYA KAPULAGA DI BAWAH TEGAKAN KEBUN HUTAN KEPADA PETANI GAPOKTANHUT PUJO MAKMUR, LAMPUNG - INDRIYANTO, INDRIYANTO; TSANI, MACHYA KARTIKA; SANTOSO, TRIO; SURNAYANTI, SURNAYANTI; DAMAYANTI, INGGAR (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2024)
Forest farmers, members of a combination of Pujo Makmur forest farmer groups, Lampung Province, do not yet know how to cultivate cardamom correctly in the Pematang Kubuato protected forest area. The technical guidance was carried out to increase forest farmers' knowledge about the correctly cultivation of cardamom under forest garden stands. The methods used in implementing technical guidance were lectures and discussions, as well as inspection of cardamom planting areas. Changes in farmer knowledge were evaluated through pre test and post test with questionnaires. The results of technical guidance activities for forest farmers were that forest farmers' knowledge regarding how to prepare cardamom seedlings increased by 18.8, forest farmers' knowledge regarding how to plant cardamom under forest garden stands increased by 19.0, forest farmers' knowledge regarding how to care for cardamom plants increased by 19.0. 18.6, forest farmers' knowledge of how to harvest cardamom fruit increased by 16.2, and forest farmers' knowledge of how to handle post-harvest fruit increased by 16.8. All forest farmers (100% of participants) stated that they were determined to implement cardamom cultivation correctly. It can be concluded that this technical guidance has succeeded in increasing farmers' knowledge and interest regarding various aspects of cardamom cultivation. ABSTRAKPetani hutan anggota Gapoktanhut Pujo Makmur, Provinsi Lampung belum mengetahui cara budidaya kapulaga secara benar dalam kawasan hutan lindung Pematang Kubuato. Bimbingan teknis bertujuan untuk meningkatkan pengetahuan petani hutan tentang budidaya kapulaga secara benar di bawah tegakan kebun hutan. Metode yang digunakan dalam pelaksanaan bimbingan teknis adalah ceramah dan diskusi, serta peninjauan areal pertanaman. Perubahan pengetahuan petani dievaluasi menggunakan kuesioner pada awal dan akhir kegiatan bimbingan teknis. Hasil kegiatan bimbingan teknis kepada petani hutan adalah pengetahuan petani hutan mengenai cara penyiapan bibit kapulaga meningkat sebesar 18,8, pengetahuan petani hutan mengenai cara penanaman kapulaga di bawah tegakan kebun hutan meningkat sebesar 19,0, pengetahuan petani hutan mengenai cara pemeliharaan tanaman kapulaga meningkat sebesar 18,6, pengetahuan petani hutan mengenai cara pemanenan buah kapulaga meningkat sebesar 16,2, dan pengetahuan petani hutan mengenai cara penanganan buah pascapanen meningkat sebesar 16,8. Semua petani hutan (100% peserta) menyatakan bertekat akan menerapkan budidaya kapulaga secara benar. Dapat disimpulkan bahwa bimbingan teknis ini berhasil meningkatkan pengetahuan dan minat petani mengenai berbagai aspek budidaya tanaman kapulaga.